"We don't do it for the money" … The scale and reasons of poverty‐pay among frontline long‐term care workers in England. (12th June 2017) - Hussein, Shereen
Abstract: Demographic trends escalate the demands for formal long‐term care (LTC) in the majority of the developed world. The LTC workforce is characterised by its very low wages, the actual scale of which is less well known. This article investigates the scale of poverty‐pay in the feminised LTC sector and attempts to understand the perceived reasons behind persisting low wages in the sector. The analysis makes use of large national workforce pay data and a longitudinal survey of care workers, as well as interviews with key stakeholders in the sector. The analysis suggests that there are at least between 10 and 13% of care workers who are effectively being paid under the National Minimum Wage in England. Thematic qualitative analysis of 300 interviews with employers, care workers and service users highlight three key explanatory factors of low pay: the intrinsic nature of LTC work, the value of caring for older people, and marketisation and outsourcing of services.